2013
DOI: 10.1039/c3dt50513h
|View full text |Cite
|
Sign up to set email alerts
|

Improving the bioactivity of Zn(ii)-curcumin based complexes

Abstract: New Zn(II)-curcumin based heteroleptic complexes (1-5) have been synthesized and fully characterized, with the aim to improve the bioactivity of the precursor derivative [(bpy-9)Zn(curc)Cl] (A), a potentially intercalating antitumor agent recently reported. Some structural changes have been made starting from the reference complex A, in order to introduce new functionalities, such as electrostatic and/or covalent interactions. In particular, keeping the same N,N chelating ligand, namely bpy-9, two completely d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 31 publications
4
79
0
1
Order By: Relevance
“…These results support the findings that Zn-curc treatment was indeed restoring wtp53 transcriptional activity. As Zn-cur complex previously showed increased biological activity compared to curcumin alone [13,14], here we tested the effect of curcumin (curc) on p53 reactivation. We found that curcumin alone did not induce wtp53 target gene transcription (Figure 2F), suggesting that the effect of Zn-curc on mtp53 reactivation was mainly depended on Zn(II) ability to induce mtp53 reactivation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These results support the findings that Zn-curc treatment was indeed restoring wtp53 transcriptional activity. As Zn-cur complex previously showed increased biological activity compared to curcumin alone [13,14], here we tested the effect of curcumin (curc) on p53 reactivation. We found that curcumin alone did not induce wtp53 target gene transcription (Figure 2F), suggesting that the effect of Zn-curc on mtp53 reactivation was mainly depended on Zn(II) ability to induce mtp53 reactivation.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we took advantage of the fluorescent feature of the Zn-curc compound [13,14] to evaluate its intratumoral localization. To this aim we used human U373 glioblastoma cells engineered with luciferase reporter (U373-LUC) for imaging analysis [22].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…22, 23, 24, 25, 26, 27 However, whether zinc supplementation might also affect mutp53 protein levels has never been addressed. Here, we asked whether a novel curcumin-based zinc compound (Zn(II)-curc), 28, 29 able to reactivate mutp53 proteins, 27 could modify mutp53 stability. We specifically analyzed conformation defective R175H p53 mutant (p53H175) because it is one of the most frequently and vastly studied p53 mutant, which not only exhibits dominant-negative activities over wtp53 but also possesses GOF properties.…”
mentioning
confidence: 99%